COVID-19 OUTBREAK IMPACT ON STOCK RETURN IN INDONESIA AND MALAYSIA - Merinda Wijaya; Robin Robin; Hesniati Hesniati (Universitas Internasional Batam, 2022)
The COVID-19 outbreak drastically impact worldwide economic including the stock returns. This study use Indonesia and Malaysia cases with total 141.585 and 219.381 observations in 2020. The measurement of COVID-19 of this study uses daily new confirmed cases and daily death cases from each country. To test the hypothesis, unbalanced panel and multiple regression is used to test the crowded data. The results show differ result for each country. In Indonesia, we found that the COVID-19 outbreak is strong negatively effect to stock return, in contrast, Malaysia found to be less influence. Furthermore, the effect of Monday and Friday was used to test any impact of day during the pandemic on stock return. Surprisingly, the effect of Friday affects differently from Monday. The weekend-effect still occur in pandemic situation and the investor mood still sentiment to Indonesia’s stock market.